Rancang Bangun Sistem Penjadwalan Pembelajaran Menggunakan Metode Algoritma Genetika Di Smk Multi Mekanik Masmur - Taufik, Irfan; Benny Herlandy, Pratama; Novalia, Melly (Universitas Muhammadiyah Riau, 2024)
In building an algorithm-based automatic scheduling system that has the objectives of designing an Information System-based learning scheduling system and determining the subjects applied using genetic algorithms, using Research and Development research methods, in the field of Education, (R&D) is the process of developing and product validation. The development stage consists of several stages including the potential and problem stage, the data collection stage, the Information System product design stage, the Information System validation stage, the Genetic Algorithm validation stage, the Genetic Algorithm-based Information System revision stage and Information System testing, summary of results This scheduling system makes a Java-based scheduling information system using the NetBeans application, its components consist of input Subjects, Teachers, Classrooms and the number of Chromosomes to be, and the conclusion is that an algorithm-based scheduling system can help complete scheduling in SMK Multi Mekanik Masmur schools. Pekanbaru Keywords: Genetic Algorithm, Scheduling, R&